In silco characterization of selected orchids, sesquiterpene synthases - Nurul Afiqah, Azfi (2025)
The structural and functional characterization of sesquiterpene synthases (STSs), which are essential enzymes in the biosynthesis of terpenoid compounds, is still lacking, especially in orchids. Using computational techniques like as molecular docking and homology modeling, this study fills the information gap by forecasting the ligand-binding processes and three-dimensional structures of six representative orchid STSs. The Vanda Mimi Palmer STS achieved 100% sequence identity in BLASTp analysis, and other important proteins examined include sesquiterpene synthases from Vanda Mimi Palmer, Vanda Small Boy Leong, and Phalaenopsis equestris. Phylogenetic studies have shown that orchid STSs are evolutionarily maintained and distinct from their non-orchid counterparts due to their diversification within the Orchidaceae family. SWISS-MODEL, Phyre, and BLAST-PDB were used for homology modeling, which determined that 7XKW was the best template because of its high sequence identity (up to 45%) and structural significance. ERRAT, PROCHECK, and VERIFY 3D quality evaluation verified SWISS-MODEL's excellence in producing dependable, stereochemically accurate models. At conserved active regions (R1 and R2), molecular docking experiments demonstrated substantial binding affinities for important ligands including farnesyl pyrophosphate (S1) and germacrene D (P1). Other ligands, such as linalool and ocimene, showed lesser affinities, whereas these ligands showed consistent binding patterns and interactions that are essential for sesquiterpene production. The results offer a thorough comprehension of the structural characteristics and enzymatic processes of orchid STSs. This study lays the groundwork for future experimental verification, supporting the investigation of STS functionality and biotechnology applications, specifically in terpenoid synthesis and scent generation. The work highlights how in silico methods may be used to advance structural biology and uncover the secondary metabolites found in plants' biotechnological potential.